Unraveling the Origin of the Long Fluorescence Decay Component of Cesium Lead Halide Perovskite Nanocrystals - Becker, Michael A. (ACS Nano, 2020)
[Image: see text] A common signature of nearly all nanoscale emitters is fluorescence intermittency, which is a rapid switching between “on”-states exhibiting a high photon emission rate and “off”-states with a much lower rate. One consequence of fluorescence intermittency occurring on time scales longer than the exciton decay time is the so-called delayed photon emission, manifested by a long radiative decay component. Besides their dominant fast radiative decay, fully inorganic cesium lead halide perovskite quantum dots exhibit a long fluorescence decay component at cryogenic temperatures that is often attributed to the decay of the dark exciton. Here, we show that its origin is delayed photon emission by investigating temporal variations in fluorescence intensity and concomitant decay times found in single CsPbBr(3) perovskite quantum dots. We attribute the different intensity levels of the intensity trace to a rapid switching between a high-intensity exciton state and an Auger-reduced low-intensity trion state that occurs when the excitation is sufficiently strong. Surprisingly, we observe that the exponent of this power-law-dependent delayed emission is correlated with the emission intensity, which cannot be explained with existing charge carrier trapping models. Our analysis reveals that the long decay component is mainly governed by delayed emission, which is present in both the exciton and trion state. The absence of a fine structure in trions clarifies the vanishing role of the dark exciton state for the long decay component. Our findings are essential for the development of a complete photophysical model that captures all observed features of fluorescence variations in colloidal nanocrystals.